Analisis Pembentukan Karakter Siswa di SDN Tangerang 15 - Ita Utami; Amalia Muthia Khansa; Elfrida Devianti (FONDATIA, 2020)
This study aims to find out what are the influences of the character of students in SDN TANGERANG 15. And find out what are the things that can affect the character education of students at the SDN. The method used in this research is descriptive qualitative method. The results of the analysis of this study note that the most important factors affecting the character of students are family, teacher, the environment, and learning media. If one of them is absent, the formation of student character will not shape properly, because the teacher, learning media, and learning models of students have a large role in shaping student character. To support this, teachers should strengthen their character. Next, the most important factor is love and support from family. Because if there is no support from the family, it will hamper a process of forming student character. That inhibits the formation of student character, namely when there is no harmony in a family.